(untitled) (Journal of the College of Education for Women, 2019)
The goal of current research is marked "student services for the university student at the Faculty of Education for Girls at Baghdad University in light of the overall quality indicators)" to identify the relative importance of the availability of student services offered by the College of Education at the University of Baghdad, from the viewpoint of the students. The research was Aaguetdy followers researcher Find descriptive approach to suitability research topic and in order to achieve the purposes of research, the researcher designed questionnaire examined consisted of (18) items and has been questionnaire on arbitrators and experts to verify the validity and reliability that’s been applied to the questionnaire on a group of students from the College of Education for Girls, as the sample of research (200 students) and hired a researcher statistical bagful to analyze the sample and Binaaly members responses responses respondents was reached following results: Shall the quality of student services provided to students in light of the quality indicators between the middle and the weak has got only three services on the strength of the research sample : is the paragraph (2) and (4) and (6) while you do not get the rest of the services in the paragraphs of the remaining fifteen resolution on the strength of the research sample, and perhaps it was due to lack of awareness level of services provided to students, which led to the reluctance of many students to the useof student services available and the basis of the conclusions have been some recommendations from the development of the most important-The need to raise the level of services provided to university students with the need to work hard to be the privacy of Education Girls gateway to the satisfaction of students about the quality of services provided .-Providing more efforts to raise awareness of student services and areas and their importance, to help the students to take advantage of these services in accordance with the conditions of the university